Risk Factors in Adult Myopia in Macedonia - Ljubic, Antonela; Dimitrova, Galina; Trajkovski, Vladimir; Stankovic, Branislav; Djordjievska, Ana (Scientific Foundation SPIROSKI, 2024)
AIM: In our case–control study of the Caucasian Macedonian myopia population of adults aged over 40 years, to analyze the environmental risk factors such as education level and outdoor activity levels in hours. MATERIALS AND METHODS: We included 53 patients with myopia and 64 control subjects. The following demographic characteristics were evaluated using questionnaires: Age, gender, level of education, outdoor activities (hours), and parental myopia. Ophthalmic examination was performed with slit-lamp biomicroscopy and parameters: best corrected visual acuity, cycloplegic autorefraction, and corneal curvature radius were recorded. RESULTS: About 54.7% of the myopia study population were male, and most of the subjects had high education (58.5%). About 43.4% of the myopia subjects did have parental myopia in the family history. The mean age of onset of myopia was 22.5 years, and the mean age when myopia stopped was 37.1 years. The mean value of near tasks (screen time, reading, etc.) time in hours, in the myopia group was 5.6, whereas in the emmetropia group 4.9. The mean value of outdoor activity in hours per day (prior 26 years of age, recent years, and today) was: 5.1 h, 4.2 h, 3.9 h in the myopia group versus 4.8 h, 3.8 h, 3.3 h in the emmetropia group, respectively. CONCLUSION: The prevalence of male gender in myopia group was higher. Near task time in hours was higher in myopia group versus emmetropia group. Parental history of myopia was significantly more present in patients with myopia. Environmental risk factors such as outdoor activities in hours and level of education did not differ significantly among the groups.
Keywords: Adult myopia; Parental myopia; Near tasks time; Education level; Outdoor activity